FINANCIAL STABILITY AS A KEY CHARACTERISTIC OF THE FINANCIAL STATEMENT - L. Milutina (Вестник университета)
In the article there are various definitions of «financial stability of an enterprise» the main characteristics of this concept are going to be refined and on their basis the concept «financial stability of an enterprise» will be formulated reflecting its economic essence most accurately. The influence of a company’s financial stability on the results of its activities will be traced. The purpose, tasks and functions of financial stability of an enterprise will be defined.